PENGARUH FDR DAN ROA TERHADAP TINGKAT BAGI HASIL DEPOSITO MUDHARABAH BANK SYARIAH DI INDONESIA - Rizka Nur Wahyuni; Ferry Khusnul Mubarok; Rofiul Wahyudi (Al-Qardhu, 2022)
This study aims to determine the effect of FDR and ROA on the rate of profit sharing on mudharabah deposits at Islamic banks in Indonesia. The population in this study are commercial banks registered with the Financial Services Authority (OJK) and Bank Indonesia (BI). Sampling by taking a census. The number of samples used in this study were 8 Islamic commercial banks and their objects were 2016-2018. The test results show that the variable FDR (X1) has a significant positive effect on the rate of profit sharing for mudharabah deposits (Y) and the ROA variable (X2) has a significant positive effect on the rate of profit sharing on mudharabah deposits